The role of cluster organisations in stimulating cooperation between business and science. Experience from the Visegrad Group countries - Kowalski, Arkadiusz Michał; Kuberska, Dominika; Mackiewicz, Marta (Publishing House of Wroclaw University of Economics and Business, 2023)
Cooperation between science and business is regarded as a prerequisite for the development of innovation. The aim of this article is to provide a holistic view on the nature of business-research relations in cluster organisations in the Visegrad countries, by assessing their role in promoting this cooperation and identifying its determinants and barriers. The recognition of cluster organisations as a driver of innovation is connected with the fact that they create an environment conducive to cooperation, building trust between their members and reducing numerous barriers that limit it. This paper examines the role of cluster organisations in stimulating cooperation between business and science, providing a comparative analysis of the Visegrad countries in this respect. On the basis of in-depth interviews with managers of cluster organisations, and a survey of representatives of science-sector institutions, the authors clarified the role of cluster organisations in this process. Barriers were also diagnosed, such as the capacity constraints of R&D&I in SMEs, the cost of cooperation due to administrative overheads, differences in the organisational interest and culture. The study sheds new light on the role of cluster organisations and their members, showing that the ‘strategic innovators’ are critical to science-business cooperation. The research findings may inspire cluster organisation managers and other actors to create a common innovation ecosystem and approach, as well as encourage cluster organisation companies to implement joint research projects together with research organisations, which will result in mutual benefits for the parties involved.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 197-212
Keywords: cluster; cluster organisation; science-business cooperation; Visegrad Group